Adaptive leadership capacity in extreme contexts : the experience of public-sector leaders in South Africa during the COVID-19 pandemic - Mbokota, Gloria (University of Pretoria, 2021)
Mini Dissertation (MPhil)--University of Pretoria, 2020.